1985
DOI: 10.1016/0167-8817(85)90057-4
|View full text |Cite
|
Sign up to set email alerts
|

Microinjected photoreactivating enzymes from Anacystis and Saccharomyces monomerize dimers in chromatin of human cells

Abstract: Photoreactivating enzymes (PRE) from the yeast Saccharomyces cerevisiae and the cyanobacterium Anacystis nidulans have been injected into the cytoplasm of repair-proficient human fibroblasts in culture. After administration of photoreactivation light, PRE-injected cells displayed a significantly lower level of UV-induced unscheduled DNA synthesis (UDS) than non-injected cells. This indicates that monomerization of the UV-induced pyrimidine dimers in the mammalian chromatin had occurred as a result of photoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Yet, we have shown that rapid photoreactivation of CPDs in β‐act‐CPD photolyase transgenic mouse cells has a pronounced effect on NER, as evident from the ∼3‐fold (light‐dependent) reduction in UDS. A comparable reduction in UDS has been observed after microinjection of Anacystis nidulans CPD photolyase into cultured human fibroblasts (Zwetsloot et al ., 1985, 1986), which is somewhat surprising as rodent cells, in contrast to human cells, hardly remove CPD lesions by GG‐NER. Apparently, TC‐NER of CPD lesions constitutes a prominent portion of NER activity in the first hour after UV exposure.…”
Section: Discussionsupporting
confidence: 68%
“…Yet, we have shown that rapid photoreactivation of CPDs in β‐act‐CPD photolyase transgenic mouse cells has a pronounced effect on NER, as evident from the ∼3‐fold (light‐dependent) reduction in UDS. A comparable reduction in UDS has been observed after microinjection of Anacystis nidulans CPD photolyase into cultured human fibroblasts (Zwetsloot et al ., 1985, 1986), which is somewhat surprising as rodent cells, in contrast to human cells, hardly remove CPD lesions by GG‐NER. Apparently, TC‐NER of CPD lesions constitutes a prominent portion of NER activity in the first hour after UV exposure.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, the structure of CPD and (6 -4)PP lesions, their DNA distorting properties, and the interactions between photolysase and DNA has widened the scope for the biological impact of this unique repair enzyme system [87]. After a microinjected microbial photolyase was shown to rapidly eliminate CPD lesions in UVexposed human fibroblasts [88], in the following years several research groups generated mammalian cells transiently or stably expressing photolyases. Experiments with CPD-photolyase transgenes in normal (NER-proficient) human cell lines revealed that CPDs are an instigator of UV-mediated apoptosis [89,90].…”
Section: Photolyase In Mammalsmentioning
confidence: 99%
“…Photoreactivation is an elegant reaction to investigate DNA damage recognition in chromatin in living cells, since only one enzyme is involved in this process and its activity can be regulated precisely by light. Photoreactivation experiments with chicken embryo fibroblasts (van de Merwe and Bronk, 1981) and injection of photolyases from yeast and A.nidulans in human fibroblasts (Zwetsloot et al ., 1985) documented that a significant fraction of CPDs can be repaired despite packaging of DNA in chromatin. Another study showed that ∼75% of the DNA was shielded from photorepair immediately after UV exposure, but all sites became available after 9–12 h (Pendrys, 1983).…”
Section: Dna Repair By Photolyase In Chromatinmentioning
confidence: 99%